Effects of Strain Rate and Initial Density on the Dynamic Mechanical Behaviour of Dry Calcareous Sand - Zhangyong Zhao; Yanyu Qiu; Mingyang Wang (Shock and Vibration)
The dynamic compressive behaviour of dry calcareous sand under rigid confinement was characterised using a split-Hopkinson pressure bar (SHPB). Sand samples were confined inside a sleeve of hardened stainless steel and capped by a pair of aluminium cylindrical rods. This assembly was subjected to repeated dynamic compaction to attain precise bulk mass densities. It was then sandwiched between the incident and transmission bars of SHPB for dynamic compression testing. Sand specimens of three initial mass densities, namely, 1.26 g/cm3, 1.35 g/cm3, and 1.42 g/cm3, were loaded by incident pulses applying a stress of 35 MPa, 71 MPa, and 143 MPa, respectively. Experimental results show that in the strain rate range of 335 s−1 to 1253 s−1, the dynamic mechanical behaviours of dry calcareous sands exhibited no significant strain rate effect. The Lundborg model and the Murnaghan model could be used to describe the deviatoric and volumetric behaviours of calcareous sand with different initial densities, respectively.